Pacemaker infection and endocarditis due to Parvimonas micra: A case report and systematic review. (December 2021) - Suzuki, Takahiro; Ishikawa, Kazuhiro; Matsuo, Takahiro; Kijima, Yasufumi; Aoyagi, Hideshi; Kawai, Fujimi; Komiyama, Nobuyuki; Mori, Nobuyoshi
Abstract: Infective endocarditis caused by Parvimonas micra is rare. Its clinical features are presented in this systematic review. We also describe the case of an 82-year-old man with infective endocarditis and pacemaker infection due to P. micra . There are some reports of recurrence during antimicrobial therapy; hence, careful follow-up is necessary. Highlights: Parvimonas micra is commonly recognized as an oral pathogen. Sometimes serious complications due to P. micra infection can occur. We present a case of pacemaker infection and endocarditis due to P. micra. We also present a systematic review of endocarditis due to P. micra. Clinicians should be attentive to recurrent infection during follow-up.